Spectrum Comparison between GFDM, OFDM and GFDM Behavior in a Noise and Fading Channel - Hamiti, Enver; Sallahu, Fatlum (International Journal of Electrical and Computer Engineering Systems, 2015)
GFDM (Generalized Frequency Division Multiplexing) is a multi-carrier multiplexing scheme for next generations of cellular networks. In this paper, a simulation of the GFDM transmitter in a noisy channel will be conducted. The spectrum benefit of GFDM over OFDM (Orthogonal Frequency Division Multiplexing) is treated, which will be used in applications such as machine-to-machine communications or cognitive radio. The behavior of GFDM after passing on the AWGN (Additive White Gaussian Noise) channel for different values of SNR (Signal-to-Noise Ratio) will be observed, as well as the GFDM behavior after passing through the Rayleigh channel.